Risk factors of the depressive and anxiety disorders development amongpatients with Adolescent Idiopathic Scoliosis and possible therapeutic interventions - Tomczak, Tomasz; Rogalski, Jakub (Current Problems of Psychiatry, 2024)
Introduction: Adolescent idiopathic scoliosis is a common type of scoliosis among adolescents. A significant problem is the coexistence of depressive and anxiety disorders. However, the causes of this condition are not fully recognized. Thus, it seems reasonable to search for possible risk factors that may trigger mental disorder occurrence. Material and methods: This is a literature narrative review concentrating on the influence of the adolescent idiopathic scoliosis on the development of depression and anxiety disorders among adolescents, as well as possible therapeutic interventions. Google Scholar, Medline, PubMed and Science Direct databases were searched throughout January 2024 for relevant original and review articles from 2000 to 2024, using the following keywords: “adolescent idiopathic scoliosis”, “anxiety”, “body image”, “bracing”, “chronic disease”, “depression”, “mental disorders”, “pain”, “peer relationship”, “physical activity”, “pulmonary function”, “sleep disorders”, “surgery”, “treatment”. Manuscripts in other language than Polish or English were excluded from the search. To ensure the appropriate quality of this review, the Scale for the Assessment of Narrative Review Articles was used. Results: Chronic pain, sleep disorders, pulmonary function impairment, perception of the disease as a chronic somatic disease, disturbed body image, lack of social interactions, physical activity limitation and applied methods of treatment may lead to the depressive and anxiety disorders development in the adolescent idiopathic scoliosis course. Conclusions: Biological and psychosocial factors contribute to the pathogenesis of depressive and anxiety disorders among patients with adolescent idiopathic scoliosis. Their identification should help create a comprehensive plan of treatment, which may effectively maximize therapeutic outcomes in the context of both scoliosis and mental disorders.